Perbezaan maklumbalas minima dan kekerapan pengambilan giliran di antara gender dalam interaksi bilik darjah / Yogeeta A/P Yogabalan - Yogabalan, Yogeeta (2012)
The previous studies on language and gender indicate that men and women are using different languages. This is an interactive study which was conducted in a classroom full of male and female students. Therefore this study aims to evaluate the classroom interaction among primary school students as the main component to view the differences in minimal responses and turn taking among male and female students. The main objective of this study is to identify the frequency of turn taking and differences in using minimal responses among the primary school students during classroom interactions. The comparisons in the frequency of turn taking during interactions among the male and female students in the classroom are assessed based on interruptions during conversations and overlapping statements. This study also evaluates and identifying the types of minimal responses during interactions among the male and female students during classes. The primary data was obtained through recorded and transcribed interactions in the classroom. The researcher used qualitative method to gathered data of minimal responses and turn taking. The researcher also used simple calculation method to identify the frequency of minimal responses and turn taking by analyzing the obtained data. The study shows that the male students are dominant in turn taking during interaction compared to female students who are softer and provide opportunities for male students during interactions. The female students are also found to give more minimal responses during interactions. This study generally contributes to the field of linguistics and influences other researchers to conduct extensive studies especially on language, gender and education.